Latest developments in silica-based thermoluminescence spectrometry and dosimetry. (November 2016) - Bradley, D.A.; Jafari, S.M.; Siti Shafiqah, A.S.; Tamcheck, N.; Shutt, A.; Siti Rozaila, Z.; Abdul Sani, S.F.; Sabtu, Siti Norbaini; Alanazi, Abdulaziz; Amouzad Mahdiraji, G.; Abdul Rashid, H.A.; Maah, M.J.
Abstract: Using irradiated doped-silica preforms from which fibres for thermoluminescence dosimetry applications can be fabricated we have carried out a range of luminescence studies, the TL yield of the fibre systems offering many advantages over conventional passive dosimetry types. In this paper we investigate such media, showing emission spectra for irradiated preforms and the TL response of glass beads following irradiation to an 241 Am–Be neutron source located in a tank of water, the glass fibres and beads offering the advantage of being able to be placed directly into liquid. The outcomes from these and other lines of research are intended to inform development of doped silica radiation dosimeters of versatile utility, extending from environmental evaluations through to clinical and industrial applications. Highlights: We provide a status report for our work on silica-doped media for TL dosimetry. The construction and performance of a TL emission spectra facility is described. Oxygen-rich/oxygen deficient Ge-doped SiO2 defects/lattice relaxation phenomena are related to TL spectra. Ge-doped SiO2 are used to obtain high spatial-resolution Am–Be neutron source measurements.